Pengetahuan Perawat dalam Pelaksanaan Komunikasi SBAR pada Saat Handover - Titileviana Manalu; Siti Anisah Anisah; Intan Pertiwi; Farida Murtiani (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background : The application of SBAR communication is one of the efforts to improve patient safety in hospitals. The purpose of the study was to determine the relationship between nurses' knowledge and the implementation of SBAR communication at the time of handover at RSPI Prof. Dr. Sulianti SarosoMethods : Quantitative research with cross sectional design. The sample in this study were nurses at RSPI Prof. Dr. Sulianti Saroso as many as 101 people who were taken by purposive sampling technique. Data analysis was carried out univariate and bivariate with chi square test.Results : The results of the study found that from 101 respondents, it was known that most of the knowledge about SBAR communication was good, namely 82 respondents (81.2%). The implementation of SBAR communication during handover was mostly effective, namely 66 respondents (65.3%).Conclusion : There is a relationship between knowledge and the implementation of SBAR communication during patient handover (Pvalue = 0.036), thus nurses are expected to increase knowledge in order to carry out SBAR communication effectively during handover.